Impact of the Pandemic on the Development of E-Commerce - Szczukocka, Agata (Acta Universitatis Lodziensis. Folia Oeconomica, 2022)
In recent years, we have observed a dynamic development of the service sector, especially e‑commerce. This is due to the development of new technologies, better internet access and the evolution of consumer habits. E‑commerce has made shopping faster and more convenient and safer during the COVID–19 pandemic. The aim of the study is to assess the impact of the pandemic on the level of development of e‑commerce in Poland. The article explains the concept of e‑commerce, presents the advantages and disadvantages of this form of sales from the point of view of the buyer and seller, and the dynamics of e‑commerce development before and after the COVID–19 pandemic. The data presented in the article and their analysis indicate an upward trend in e‑commerce in Poland. The analysis of trends and research results shows that e‑commerce in Poland is developing at a fast pace, has a great growth potential and will evolve depending on the clients’ needs. The pandemic is believed to have accelerated the pace of customers switching from traditional, stationary to online shopping. After the lockdown was lifted, no decrease in the number of purchase transactions was observed.